THE INFLUENCE OF TRANSFORMATIONAL LEADERSHIP STYLE AND WORK ENVIRONMENT ON EMPLOYEE PERFORMANCE THROUGH MOTIVATION AS AN INTERVENING VARIABLE IN MANUFACTURING INDUSTRY - Resa Dwi Jayanti; Dina Novita (P3I UMSurabaya, 2024)
The background of this research is leaders who free employees to innovate, but do not meet the standards expected by the company, and a work environment that does not mutually provide positive energy to each employee. The impact of the problem resulted in a decrease in production results produced by employees so that the performance provided was not optimal, and as a result, there were many complaints from consumers. The purpose of this study is to determine the effect of transformational leadership style and work environment on employee performance through motivation as an intervening variable in the manufacturing industry. The research method used is quantitative research using a saturated sample with a total of 57 employees as respondents. In this study, the research instrument used was a questionnaire and the data analysis used was SEM using the SmartPLS 4 application. The results of this study indicate that (1) there is a significant influence of transformational leadership on employee performance. (2) There is a significant influence of Transformational Leadership on Motivation. (3) There is no significant effect of the Work Environment on Employee Performance. (4) There is a significant effect of the work environment on motivation. (5) There is a significant effect of motivation on employee performance. (6) Variable Motivation intervenes and has a significant influence on Transformational Leadership and Employee Performance. (7) Variable Motivation intervenes and has a significant effect between the Work Environment and Performance.